2020
DOI: 10.3847/1538-4357/ab5a7f
|View full text |Cite
|
Sign up to set email alerts
|

Model-independent Reconstruction of f(T) Gravity from Gaussian Processes

Abstract: We apply Gaussian processes and Hubble function data in f (T ) cosmology, to reconstruct for the first time the f (T ) form in a model-independent way. In particular, using H(z) datasets coming from cosmic chronometers as well as from the radial BAO method, alongside the latest released local value H0 = 73.52 ± 1.62 km/s/Mpc, we reconstruct H(z) and its derivatives, resulting eventually in a reconstructed region for f (T ), without any assumption. Although the cosmological constant lies in the central part of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(95 citation statements)
references
References 143 publications
(116 reference statements)
6
89
0
Order By: Relevance
“…[41] for a review). Also, the fðTÞ theories have been shown to be a strong and viable modified gravity candidate alternative to GR [42][43][44][45][46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…[41] for a review). Also, the fðTÞ theories have been shown to be a strong and viable modified gravity candidate alternative to GR [42][43][44][45][46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…For a detailed overview one can refer to the Gaussian Process website. 1 In cosmology, GP has attracted a wide application in reconstructing or testing models without an a priori fiducial model [9,24,[37][38][39][40][41][42][43][44][45][46][47]. For a pedagogical introduction to GP, one can refer to Seikel et al [37].…”
Section: The Methodologymentioning
confidence: 99%
“…The red dots represent the known observational HðzÞ data, and it is the same as in Ref. [42]. The left-hand side represents the comparison for the model given by Eq.…”
Section: B Modelmentioning
confidence: 99%
“…It has been shown that some of the interacting dynamical models existing on the market can be used to solve the issue. On the other hand, a modification of General Relativity can also propose solutions [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] (to mention some references). In this paper we discuss another approach to address this issue.…”
Section: Introductionmentioning
confidence: 99%